Increasing the Provision of Choices within an Adult Transition Program - Schwartz, Rachel J.; Robertson, Rachel E.; Westerfield, Sarah (Education and training in autism and developmental disabilities, 2020)
Opportunities for choice often become limited as individuals with disabilities age. Previous research reports that staff practices directly influence choice-making opportunities for adults with disabilities. Given the link between choice-making and staff behavior, more research is needed on training staff in postsecondary settings in providing choice-making opportunities. The present study trained staff in a community transition program to facilitate diverse choice opportunities for consumers. Researchers conducted a multiple-baseline-across-participants single-subject design to evaluate the effects of a staff-training package on the frequency and diversity of choices offered by staff to consumers. Findings show that staff increased the frequency and diversity of choices offered. The potential implications of this training package for special education are discussed.